Answer:
The angle measure of one part will be 60.

360/6 = 60

That is because the circle it divided into 6 equal parts and the whole circle is 360.

Hope this helps :)

360/6 = 60

That is because the circle it divided into 6 equal parts and the whole circle is 360.

Hope this helps :)

An architect uses a scale of 2/3inch to represent 1 foot on a blueprint for a building. If the east wall of the building is 24 feet long, how long (in inches) will the line be on the blueprint?

Identify equations from visual models (hangerThe hanger image below represents a balanced equation.рpрWrite an equation to represent the image.

Write the slope-intercept form of the equation : a) 4x-2y = 3

0.8 divided by 405.2

MacGyver wants to estimate the width of a river so he can get to the other side to save the world. He makes the measurements pictured. How wide is the river? Will he be able to do it?

Identify equations from visual models (hangerThe hanger image below represents a balanced equation.рpрWrite an equation to represent the image.

Write the slope-intercept form of the equation : a) 4x-2y = 3

0.8 divided by 405.2

MacGyver wants to estimate the width of a river so he can get to the other side to save the world. He makes the measurements pictured. How wide is the river? Will he be able to do it?

**Answer:**

See Below:

**Step-by-step explanation:**

Average is take by adding all the terms together and dividing by the number of terms. In this case it terms is people in the room.

22= (25+18+17+13+24+x)/6

Where 22 is the average age. The numerator is all the known ages added together, plus x which is the age of the person who just entered. Divided by 6 because you are finding the average age of 6 people.

22 = (25+18+17+13+24+x)/6 Multiply both sides by 6

132= 97+ x Subtract 97 from both sides.

35 = x

The person who just entered the room is 35 years old.

To solve this, we first find the **total **age of the original five people, then the total age of all six with the given mean age. By subtracting these, we find that the age of the person who entered is 35 years old.

This problem can be solved using simple arithmetic. First, we calculate the total age of the first 5 people, which is 25 + 18 + 17 + 13 + 24 = 97 years. Then, we need to determine the total age of all 6 people. We're told the mean (average) age of these 6 people is 22. We find the total by multiplying the mean by the number of people, so 22 * 6 = 132 years. Finally, to find the age of the person who entered the room, we subtract the total age of the first 5 people from this new total, i.e. 132 - 97 = **35 years**. So, the person who entered the room is 35 years old.

#SPJ3

**Answer:**

**Option D**

**Step-by-step explanation:**

Given f(x) =

g(x) = 2x + 3

Since,

This function is defined for the denominator is not equal to zero.

(2x + 3) ≠ 0

x ≠

Therefore, **Option D** will be the correct option.

x= original price

% off= 20%

Sale $= $680

STEP 1:

Find discount amount

Discount Amount= % off * Original $

= 20% * x

change % to decimal (% ÷ 100)

= 0.20 * x

= 0.20x

STEP 2:

Find sale price

Sale Price= Original $ - Discount

= x - 0.20x

= 0.80x

STEP 3:

Sale= $680= 0.80x

Solve for x

$680= 0.80x

divide both sides by 0.80

$680/0.80= x

$850= x

ANSWER: The original price is $850

Hope this helps! :)

% off= 20%

Sale $= $680

STEP 1:

Find discount amount

Discount Amount= % off * Original $

= 20% * x

change % to decimal (% ÷ 100)

= 0.20 * x

= 0.20x

STEP 2:

Find sale price

Sale Price= Original $ - Discount

= x - 0.20x

= 0.80x

STEP 3:

Sale= $680= 0.80x

Solve for x

$680= 0.80x

divide both sides by 0.80

$680/0.80= x

$850= x

ANSWER: The original price is $850

Hope this helps! :)

**Answer:**

D) -4x-1

**Step-by-step explanation:**

-1(2x+3)-2(x-1)

-2x-3-2x+2

-4x-1

Therefore D is correct

b. how old is Brandon

c. what was the difference in their ages 5 years ago?

d. what is the sum of their ages now?

e. what will the sum of their ages be two years from now?

f. what will the difference of their ages be two years from now

will mark the brainliest.

Answer: See explanation

Step-by-step explanation:

a. how old is Cheryl?

Cheryl's age = d + 5

b. how old is Brandon?

d + 5 + 2

= d + 7

c. what was the difference in their ages 5 years ago?

Cheryl age five years ago = d

Brandon's age five years ago = d + 2

Difference = d + 2 - d = 2 years

d. what is the sum of their ages now?

Cheryl's age = d + 5

Brandon age = d + 7

Sum = d + 5 + d + 7

= 2d + 12

e. what will the sum of their ages be two years from now?

Two years from now,

Cheryl's age = d + 5 + 2 = d + 7

Brandon age = d + 7 + 2 = d + 9

Sum = d + 7 + d + 9

= 2d + 16

f. what will the difference of their ages be two years from now

Two years from now,

Cheryl's age = d + 5 + 2 = d + 7

Brandon age = d + 7 + 2 = d + 9

Difference = Brandon age - Cheryl age

= (d + 9) - (d + 7)

= 2 years.

B. -16t^2+1000<_ 300

C. -16t^2+1000>_300

D.-16t^2+1000>300

**Answer:**

D. is the correct answer.

**Step-by-step explanation:**

It is given that Distance, d above ground with time 't' is given by the formula:

The **negative sign** with indicates that **the distance is decreasing** with **square of time**. i.e. value is getting subtracted from a value 1000.

For example, if t = 0, d = 1000 feet

If t = 2, d = -16 4 + 1000 = 936 feet

We can clearly see that when **'t' is increasing, the distance 'd' is decreasing**.

And at a certain time, the object will be on ground when d = 0 feet.

Inequality for the distance greater than 300 feet i.e.

d > 300 feet

Hence, the inequality will be:

is the * correct answer*.